2014
DOI: 10.1371/journal.pone.0102095
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glucose Metabolism by Balanced Deep-Sea Water Ameliorates Hyperglycemia and Pancreatic Function in Streptozotocin-Induced Diabetic Mice

Abstract: The aim of this study was to determine the effects of balanced deep-sea water (BDSW) on hyperglycemia and glucose intolerance in streptozotocin (STZ)-induced diabetic mice. BDSW was prepared by mixing DSW mineral extracts and desalinated water to yield a final hardness of 1000–4000 ppm. Male ICR mice were assigned to 6 groups; mice in each group were given tap water (normal and STZ diabetic groups) or STZ with BDSW of varying hardness (0, 1000, 2000, and 4000 ppm) for 4 weeks. The STZ with BDSW group exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Previously, our studies on the antidiabetic effects of balanced deep-sea water (BDSW) have shown that hyperglycemia and glucose tolerance were improved by accelerating glucose uptake, along with the suppression of glucose production-related genes, and a recovery of pancreatic function in experimental animal models of obesity and non-obesity type diabetes mellitus [21,22]. Based on the efficacy of BDSW in cell and animal experiments, the clinical trial presented here was conducted to evaluate the efficacy of BDSW on glycemic and insulin-sensitivity parameters, as well as its safety.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our studies on the antidiabetic effects of balanced deep-sea water (BDSW) have shown that hyperglycemia and glucose tolerance were improved by accelerating glucose uptake, along with the suppression of glucose production-related genes, and a recovery of pancreatic function in experimental animal models of obesity and non-obesity type diabetes mellitus [21,22]. Based on the efficacy of BDSW in cell and animal experiments, the clinical trial presented here was conducted to evaluate the efficacy of BDSW on glycemic and insulin-sensitivity parameters, as well as its safety.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the expression of glucose uptake-related genes in the skeletal muscle of diabetes mouse was upregulated by DSW treatment. Thus, LKB1, AMPK, and mTOR activation was restored by DSW (Ha et al 2014b). Another study indicated that DSW could attenuate hypertension and decrease lipid accumulation by the activation of AMPK/ACC signaling (Sheu et al 2013).…”
Section: Resultsmentioning
confidence: 92%
“…There are a lot of minerals, such as calcium (Ca), magnesium (Mg), vanadium (V), zinc (Zn), and potassium (K). Many studies have shown that DSW can be effectively used to treat diabetes, obesity, hyperlipidemia, and hypertension (Sheu et al 2013;Ha et al 2014b;Li et al 2014;Yang et al 2014). Mg supplementation improves myocardial metabolism and inhibits myocardial cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It is known from studies in mice, that oral magnesium supplementation increases the number of glucose transporters in the cell membrane of muscle cells; glucose can therefore be imported faster and more effectively [ 60 ].…”
Section: Discussionmentioning
confidence: 99%